Multi-source residual capacity collaborative dynamic compensation strategy based on robust residual generator. (November 2021) - Li, Tiecheng; Su, Can; Zhang, Yue
Abstract: In this paper, a dynamic compensation strategy based on a residual generator was proposed to solve the problem of the power quality of the bus in an isolated AC microgrid. Firstly, the disturbance analysis of power quality problems such as voltage fluctuation, three-phase imbalance, harmonic wave is carried out, and the disturbance current is converted into the time domain function in the dq rotating coordinate system. Secondly, the inverter establishes the state space model under the dq rotation coordinate system. Then, the control structure based on residual generator is proposed, the voltage compensator is solved by model matching method, and the current loop secondary compensator is designed to eliminate the influence of the voltage compensator on the current loop. Thirdly, the residual capacity calculation method of the inverter is analysed, and the residual capacity is used to achieve the power quality collaborative governance on the parallel inverter system with the perturbation allocation method. Finally, the control strategy proposed in this paper is verified by the simulation built in PSCAD/EMTDC, and the results can be effectively applied to the low-level control of microgrid, and the power quality control effect of voltage fluctuation, three-phase unbalance and harmonics is good, which improves the robustness of the system to a certain extent.